Interception of pathogens during quarantine processing: an effort towards safe import of oilseed and vegetable Brassicas germplasm in India - Jameel Akhtar,; Baleshwar Singh,; A Kandan,; Pardeep Kumar,; AK Maurya,; SC Dubey, (Journal of Oilseed Brassica, 2026)
During 1976-2015, a total of ~75000 seed samples of oilseed and vegetable Brassicas germplasm receivedfrom different countries were processed for quarantine clearance. Seed health testing resulted in interceptionof 17 pathogenic fungi and one bacterium in 2628 samples from 23 countries. Decade wise (1976-1985;1986-1995; 1996-2005; 2006-2015) analysis revealed the highest level infections in 948 (36.3%) during 1986-1995 followed by 912 interceptions (34.9%) during 1996-2005 and lowest level of infections was interceptedin 176 samples (6.7%) during 2005-2016. Risk analysis of the interceptions showed that among the pathogens,Alternaria brassicicola was recorded in most of the infected samples (65.5%) followed by Xanthomonascampestris pv. campestris (17.8%). Among countries, maximum interceptions were made from USA (26.3%)followed by Canada (24.0%) which indicated that there is the highest risk of introduction of pathogens alongwith Brassicas seeds from USA and Canada. Among pathogens intercepted, Leptosphaeria maculanscausing black leg from Australia and Canada and X. c. pv. campestris causing black rot of crucifers fromCanada are potential quarantine pathogens to India, hence the samples infected with L. maculans andFusarium solani were rejected and incinerated and samples infected with X. c. pv. campestris were salvagedby giving hot water treatment at 500C for 20 min. before their release. Whereas, samples infected with otherpathogens viz., A. brassicae, A. brassicicola, A. raphani, A. solani, Bipolaris sorghicola, B. sorokiniana,Botrytis cinerea, Cephalosporium maydis, F. oxysporum, F. verticillioides, Phoma sorghina, Rhizoctoniabataticola, Sclerotium rolfsi, Verticillium albo-atrum were salvaged using fungicidal seed treatment beforetheir release. This could finally prevent entry or minimized spread of exotic pathogens into the country andalso promoted germplasm exchange for crop improvement. The interceptions of pathogens of quarantinesignificance to India from different countries emphasizes the need of critical examination of imported oilseedand vegetable Brassicas during the quarantine processing to safeguard our experimental as well as agriculturalfields from inadvertent introduction of associated pathogens or more virulent races/ strains of the existingones in the country.